Relationship between psychosocial dimensions of personality and perception of anxiety, with injury history in elite athletes - Peñaranda-Moraga, M.; García-De Frutos, J. M.; Nadal-Nicolás, Y.; Cuestas-Calero, B. J.; Martínez-Rodríguez, A.; Yáñez-Sepúlveda, R.; Cortés-Roco, G.; López-Gil, J. F.; Muñoz-Villena, A. J. (Frontiers in Sports and Active Living, 2026)
Introduction: High-performance sports practice involves both physical challenges and psychosocial factors that influence the performance and well-being of athletes. In this context, both genetic and cultural/social dimensions of personality and the perception of anxiety play a fundamental role in the sporting experience, especially when related to the history of sports injuries.